Comparative study of material point method and upper bound limit analysis in slope stability analysis. Issue 1 (30th June 2020) - Zhao, Lianheng; Qiao, Nan; Zhao, Zhigang; Zuo, Shi; Wang, Xiang
Abstract: The upper bound limit analysis (UBLA) is one of the key research directions in geotechnical engineering and is widely used in engineering practice. UBLA assumes that the slip surface with the minimum factor of safety (FSmin) is the critical slip surface, and then applies it to slope stability analysis. However, the hypothesis of UBLA has not been systematically verified, which may be due to the fact that the traditional numerical method is difficult to simulate the large deformation. In this study, in order to systematically verify the assumption of UBLA, material point method (MPM), which is suitable to simulate the large deformation of continuous media, is used to simulate the whole process of the slope failure, including the large-scale transportation and deposition of soil mass after slope failure. And a series of comparative studies are conducted on the stability of cohesive slopes using UBLA and MPM. The proposed study indicated that the slope angle, internal friction angle and cohesion have a remarkable effect on the slip surface of the cohesive slope. Also, for stable slopes, the calculation results of the two are relatively close. However, for unstable slopes, the slider volume determined by the UBLA is much smaller than the slider volume determined by the MPM. In other words, for unstable slopes, the critical slip surface of UBLA is very different from the slip surface when the slope failure occurs, and when the UBLA is applied to the stability analysis of unstable slope, it will lead to extremely unfavorable results.